A Study of Customers’ Satisfaction with Korean Dramas in Vietnam - Anh, Nguyen Hoang; Ha, Nguyen Thi Nguyet (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2019)
Along with the spread of the Korean wave (Hallyu) since the 1990s, Korean dramas have become popular worldwide and became a global phenomenon. Entering the Vietnamese market from 1996, Korean dramas have been successful in both attracting audiences’ interest and filmmakers’ attention. In order to find out the reasons behind the success of Korean films this paper explored the factors affecting Vietnamese customers’ satisfaction with Korean TV dramas. Based on the research of factors affecting customer satisfaction by different authors such as Philip Kotler, Oliver, McColl and Truong, the authors have built up a model to explore audience satisfaction with TV drama using 4 factors: actor (regarding popularity and appearance), script, music, and cultural images. To empirically test the hypotheses, 226 responses have been collected through an online questionnaire from November - December 2018 and tested by various statistical analyses, such as factor analysis, regression analysis, and ANOVA. The findings have indicated that script, music, cultural images have a correlation with Vietnamese viewers’ satisfaction with Korean dramas while actors do not affect the overall satisfaction. Based on the findings,the authors provide implications and offer suggestions to Vietnamese filmmakers on improving customer satisfaction, thereby contributing to the development of TV drama production in Vietnam.